Contact force of composite plate impacted at low energy alteration by hygrothermal conditions - RABOUH, Mustapha; ZOUGGAR, Kamel; GUERRAİCHE, Khelifa (International Conference on Applied Engineering and Natural Sciences, 2023)
Quite recently, considerable attention has been paid to the phenomena of impact. To enrich and give more light on the phenomena, this work is presented to give a comprehensive account of the effect of contact force due to an impact on composite plate subjected to an hygrothermal conditions specially those made of Glass/Polyester. A comparative study between an experimental data obtained by [1] from impact tests to those obtained by simulations was firstly conducted. Based on the obtained results, it can be concluded that model reproduce very successfully the experimental studies. The obtained numerical forces will be then used in Modde V 5.0 software to establish an DOE plan ‘design of experiments’. Two factors are taken into consideration: the absorbed mass of water by the material and the drop height of the projectile and their effects on the numerical contact force. From the results it has been carried out that the numerical contact force is reduced for aged plates. The most influencing parameter is the drop height of the projectile. An important implication of these findings is that a mathematical model is established which governs the contact force in the domain studied.